Intranasal but not subcutaneous vaccination with LaAg allows rapid expansion of protective immunity against cutaneous leishmaniasis. Issue 18 (25th April 2018) - Pereira Silva Bezerra, Izabella; Amaral Abib, Marina; Rossi-Bergmann, Bartira
Abstract: Mucosal but not parenteral vaccination with whole Leishmania amazonensis promastigotes antigens (LaAg) is known to increase host resistance to infection by an as yet unknown immune mechanism. Since early immune responses are critical for infection establishment, in the present study the differential responses elicited by subcutaneous (s.c.) and intranasal (i.n.) vaccination with LaAg were investigated during the initial stages of infection. For that, BALB/c mice were given two LaAg doses by i.n. or s.c. route prior to L. amazonensis infection in the footpad. It was found that mucosal vaccination prevented both T helper (Th) 2-associated cutaneous hypersensitivity and local interleukin (IL)-4 production in the first days after parasite challenge in the footpad. That was accompanied by increased Th1 (T-bet and IL-12) and Treg (Foxp3 and IL-10) transcription factor and cytokine expression in the lesion draining lymph nodes. In contrast, s.c. LaAg predominantly led to higher Th2 (GATA3) and transforming growth factor (TGF)-β expression. Prior i.n. vaccination was able to prevent the disease-exacerbating effect of s.c. vaccination. Although both CD4 + and CD8 + T cells were transiently increased in the cervical lymph nodes (cLN), the numbers of CD4 + Foxp3 + regulatory T (Treg ) cells decreased within 48 h of i.n. vaccination as compared to non-vaccinated mice. Adoptive transfer of such cLN cells conferred increased resistance to infected mice, mimicking the effect of i.n. vaccination. Altogether, these data indicate that i.n. vaccination with LaAg may prevent early peripheral expansion of detrimental cells normally elicited by active infection or s.c. vaccination, thus allowing full expansion of protective responses.